Hypoxia-inducible factor (HIF) asparagine hydroxylase is identical to factor inhibiting HIF (FIH) and is related to the cupin structural family. - Hewitson, K; McNeill, L; Riordan, M; Tian, Y; Bullock, A; Welford, R; Elkins, J; Oldham, N; Bhattacharya, S; Gleadle, J; Ratcliffe, P; Pugh, C; et al. (2002)
Activity of the hypoxia-inducible factor (HIF) complex is controlled by oxygen-dependent hydroxylation of prolyl and asparaginyl residues. Hydroxylation of specific prolyl residues by 2-oxoglutarate (2-OG)-dependent oxygenases mediates ubiquitinylation and proteasomal destruction of HIF-alpha. Hydroxylation of an asparagine residue in the C-terminal transactivation domain (CAD) of HIF-alpha abrogates interaction with p300, preventing transcriptional activation. Yeast two-hybrid assays recently identified factor inhibiting HIF (FIH) as a protein that associates with the CAD region of HIF-alpha. Since FIH contains certain motifs present in iron- and 2-OG-dependent oxygenases we investigated whether FIH was the HIF asparaginyl hydroxylase. Assays using recombinant FIH and HIF-alpha fragments revealed that FIH is the enzyme that hydroxylates the CAD asparagine residue, that the activity is directly inhibited by cobalt(II) and limited by hypoxia, and that the oxygen in the alcohol of the hydroxyasparagine residue is directly derived from dioxygen. Sequence analyses involving FIH link the 2-OG oxygenases with members of the cupin superfamily, including Zn(II)-utilizing phosphomannose isomerase, revealing structural and evolutionary links between these metal-binding proteins that share common motifs.